Effectiveness of weekly polymerase chain reaction-based open reading frame typing analysis of all newly isolated methicillin-resistant Staphylococcus aureus strains for controlling nosocomial infections. Issue 11 (November 2016) - Nakaie, Kiyotaka; Yamada, Koichi; Park, Keunsik; Nakamura, Yasutaka; Okada, Yasuyo; Fujita, Akiko; Fujimoto, Hiroki; Kaneko, Yukihiro; Kakeya, Hiroshi
Abstract: Polymerase chain reaction (PCR)-based open reading frame typing (POT) helps differentiate between bacterial strains based on the open reading frames (ORFs) of the prophage-encoding genes; multiplex PCR screening is performed to identify strains based on keeping patterns. At our hospital, surveillance of nosocomial methicillin-resistant Staphylococcus aureus (MRSA) transmission is undertaken using POT to conduct molecular epidemiological analysis for all newly detected MRSA strains. In 2014, we performed POT only once a month; however, in 2015, we increased the frequency of POT to once a week, which helped us detect nosocomial transmission that would normally be difficult to detect, and thus achieve 40% reduction in nosocomial transmission, compared to that in 2014. This suggests that weekly POT screening for all MRSA strains is one of the effective methods available for minimizing nosocomial transmission of MRSA.